Tooth Loss in Patients under Periodontal Maintenance in a Private Practice: A Retrospective Study - Stadler,Amanda Finger (2017)
Abstract The aim of the present study was to evaluate the incidence and causes of tooth loss in periodontal subjects from a private practice in Brazil. Two trained examiners extracted data from the records of subjects who sought periodontal treatment from 1980 to 2013. Only records of patients who completed the non-surgical periodontal treatment and had at least one visit for maintenance were included. Data were analyzed by chi-square test, Student’s t-test, Kaplan-Meier survival curve and Cox regression. A total of 3,319 records were reviewed and 737 records included (58.6% women, mean age of 46.6±13.0 years at the beginning of the treatment). Maintenance period ranged from 1 to 33 years (7.4±6 years). During this period, 202 individuals (27.4%) lost 360 teeth, 47.5% of losses within the first five years (n=171). Non-compliers lost more teeth than compliers (p<0.001), respectively 211 and 149 teeth. Regarding reasons of tooth loss, 84 individuals lost 38% of the teeth from periodontal disease progression (n=137). Survival analysis showed that most patients lost only one tooth from periodontal disease, and differences in the survival rates between compliers and non-compliers were observed following the second tooth loss. Approximately one-third of tooth losses was related to periodontal disease progression, and there was stability in time of the proportion of losses from disease progression and other reasons. Therefore, it is possible to conclude that compliant patients in a private practice lose fewer teeth than do non-compliers. Among compliers, periodontal disease progression was not the main cause of tooth loss.